Dividend Policy, Liquidity and Company Growth on Company Value in Pharmaceutical Companies: Kebijakan Dividen, Likuiditas dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Farmasi - Lukmawati, Ella; Hariasih, Misti (Indonesian Journal of Innovation Studies, 2023)
This study aims to examine the effect of Dividend Policy, Liquidity, and Company Growth on Firm Value. The approach used in this research is a quantitative approach. The population in this study is pharmaceutical companies listed on the Indonesia Stock Exchange. The sample in this study was 6 companies listed on the Indonesia Stock Exchange in 2016-2020 so that the data processed were 30 data with a sampling method using purposive sampling. The data used in this study is secondary data taken from the Indonesia Stock Exchange. The data analysis used is Eviews version 9. The results of this study indicate that simultaneously there is a significant influence between Dividend Policy, Liquidity, and Company Growth on Firm Value. While partially dividend policy has no effect on firm value, while liquidity has an effect on firm value and firm growth has a negative effect on firm value.